Numeracy Skills Assistance for Undocumented Children - Surya Sari Faradiba; Sikky El Walida; Surahmat; Zainal Abidin; Sunismi; Anies Fuady; Yayan Eryk Setiawan (Universitas Pendidikan Ganesha, 2023)
Numeracy is the ability to understand and use numbers and mathematical concepts in everyday life. Santri in An Nahdhoh may have problems with their numeracy skills due to various factors, including limited access to quality educational resources, traditional teaching methods that may not effectively foster understanding of mathematics, potential curriculum priorities that prioritize religious education over mathematics, language barriers, and a lack of tailored support for individual skills gaps. Students' willingness to learn numeracy skills can also be influenced by socio-economic limitations and cultural attitudes in the Santri community. Therefore, this service research aims to provide comprehensive guidance, especially to An-Nahdhah, which in the end can improve numeracy results among students. This initiative involves the participation of 25 students. This research is quantitative in nature with data analysis techniques using the t-test. Community service is important and relevant in several ways, including increasing numeracy literacy, application of religion, daily living skills, developing analytical skills, preparation for further education, increasing competitiveness, and introducing technology. This community service includes the following stages: preparation, assessment, implementation and evaluation. An-Nahdlah's numeracy support program for undocumented children offers several great benefits, particularly in helping